1999
DOI: 10.1007/s004360050618
|View full text |Cite
|
Sign up to set email alerts
|

In vivo transcriptional analysis of the spliced leader RNA gene in the trypanosomatid Leptomonas seymouri

Abstract: Gene expression in all organisms requires the direct and indirect interaction of multiple proteins with specific DNA sequence elements. Using the monogenetic trypanosomatid, Leptomonas seymouri, we investigated the cis- and trans-acting components that determine expression of a central trypanosomatid RNA, the spliced leader (SL) RNA. Using base substitution mutagenesis and DNA transfection assays, we determined that the SL RNA gene promoter lies exclusively up-stream from the transcription initiation site. Acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1999
1999
2001
2001

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…The ambiguous results of drug studies have made it extremely difficult to determine the identity of the RNA polymerase responsible for transcription of the SL RNA gene. In permeabilized trypanosomes, mRNA genes (notably α-tubulin) were downregulated by 5-10 µg/ml α-amanitin and rRNA genes required substantially more (500-1000 µg/ml) (26,47). RNA pol III-dependent small RNAs, including many of the U snRNAs, tRNA and 5S RNA, had the expected intermediate α-amanitin sensitivity; 100-200 µg/ml blocked transcription.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The ambiguous results of drug studies have made it extremely difficult to determine the identity of the RNA polymerase responsible for transcription of the SL RNA gene. In permeabilized trypanosomes, mRNA genes (notably α-tubulin) were downregulated by 5-10 µg/ml α-amanitin and rRNA genes required substantially more (500-1000 µg/ml) (26,47). RNA pol III-dependent small RNAs, including many of the U snRNAs, tRNA and 5S RNA, had the expected intermediate α-amanitin sensitivity; 100-200 µg/ml blocked transcription.…”
Section: Discussionmentioning
confidence: 97%
“…Tagetitoxin, a potent inhibitor of RNA pol III activity, had no effect on SL RNA transcription (4,25). However, α-amanitin, a low-dose inhibitor of RNA pol II, inhibited SL RNA transcription at doses higher than needed for inhibition of α-tubulin, a prototypic RNA pol II gene (3,4,26,27). The SL RNA transcript is generally not polyadenylated (28,29) and termination of SL RNA transcription requires an intact 3′ poly(T) tract, both hallmarks of RNA pol III-dependent genes (30).…”
Section: Introductionmentioning
confidence: 99%
“…Transcriptional analysis of SL RNA genes in three related trypanosomatids have shown that alterations within the SL RNA sequence had minor effects on both transcription efficiency and start site selection, although these effects were not studied in detail (5,17,27). As an important component of our Inr t studies, we determined directly if the SL RNA sequence must follow the Inr t immediately.…”
Section: In Vitro Transcription Analyses Identify Promoter Elementmentioning
confidence: 99%
“…This assignment is based on transcription elongation inhibition studies using ␣-amanitin, in which the inhibition pattern of the SL RNA most closely resembles, but does not overlap, the mRNA inhibition profile. RNA pol II-dependent mRNA gene promoters elude definition in trypanosomatids (14,17,18,27). The sequence-specific binding of PBP-1 and PBP-2 to two core SL RNA gene promoter elements argues that a subset of RNA pol II genes functions by recruiting specific DNA-binding proteins upstream from a discrete start site.…”
Section: In Vitro Transcription Analyses Identify Promoter Elementmentioning
confidence: 99%